The Identifikasi Jamur Malassezia furfur pada Kulit Petugas Kebersihan di Tempat Pembuangan Akhir (TPA) Rawa Kucing, Kota Tangerang - Istiana Annisa; Rani Jusnita; Manis Prihati; Ida Lindawati; Many Flora (Journal of Medical Laboratory Research, 2026)
Pityriasis versicolor is a superficial fungal infection caused by Malassezia furfur and is commonly found in tropical regions characterized by high temperatures and humidity. Sanitation workers at landfill sites are among the occupational groups at risk of developing fungal skin infections due to exposure to moist and unhygienic environmental conditions. This study aimed to identify the presence of Malassezia furfur in skin scrapings collected from sanitation workers at the Rawa Kucing Landfill, Tangerang City. This study employed a descriptive research design with a laboratory approach. A total of 15 skin scraping samples were collected using a purposive sampling technique from sanitation workers who exhibited skin lesions and complained of itching. Fungal identification was carried out through macroscopic examination using Sabouraud Dextrose Agar (SDA) medium and microscopic examination using Lactophenol Cotton Blue (LPCB) staining. The results showed that 6 samples (40%) were positively identified as containing Malassezia furfur, while 9 samples (60%) tested negative. Positive fungal isolates were characterized by creamy yellow colonies, round in shape with a smooth, shiny to wrinkled texture, and microscopic features consisting of clustered oval spores and short hyphae. It can be concluded that Malassezia furfur was present in the skin scrapings of sanitation workers at the Rawa Kucing Landfill, Tangerang City.